Impact of self help groups on empowerment of women: a study in dharmapuri district, tamilnadu. - R, Lakshmi; G, Vadivalagan (Journal of Management and Science, 2011)
Women empowerment is a process in which women challenge the existing norms and culture, to effectively promote their well being. The participation of women in Self Help Groups (SHGs) made a significant impact on their empowerment both in social and economical aspects This study addresses women empowerment through self help groups in Dharmapuri district of Tamilnadu . The information required for the study has been collected from both the primary and secondary sources A multistage random sampling method has been followed. Average and percentage analysis was carried out to draw meaningful interpretation of the results. Garret ranking technique was used to find the reasons for joining the Self help group. Factor analysis was used to measure the determine the relationship between the observed variables The results of the study revealed that the SHGs have had greater impact on both economic and social aspects of the beneficiaries.